2006
DOI: 10.1007/s11051-006-9096-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate materials and regulatory policy in Europe: An analysis of stakeholder perspectives

Abstract: The novel properties of nanoparticulate materials (NPM) and the rapid development of NPM based products have raised many unanswered questions and concerns by different stakeholders over its consequences for the environment and human health. These concerns have led to an increasing discussion in both the US and Europe about possible regulatory policies for NPM. In this article a comparative study of stakeholdersÕ perceptions on regulatory policy issues with NPM in Europe is presented. It was found that industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Beaudrie et al 52 in their survey of 254 US-based scientists, decisionmakers, and environmental health and safety (EHS) scientists reported that regulatory scientists did not consider themselves fully prepared to manage risks from nanotechnology applications whereas scientists and EHS experts perceived regulators to be more prepared (than the regulators' self-assessment) for managing risks from nanotechnologies. A similar uncertainty on the part of the regulators was reported in their survey of experts from both the US and Canada, 53 and also by Helland et al, 58 who gathered perceptions of experts from academic, health and safety agency and industry. Another interesting outcome observed from the interviews across the spectrum of expertise was that the questions from one area could promote discussion or even follow-up questions to colleagues from different disciplines.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Beaudrie et al 52 in their survey of 254 US-based scientists, decisionmakers, and environmental health and safety (EHS) scientists reported that regulatory scientists did not consider themselves fully prepared to manage risks from nanotechnology applications whereas scientists and EHS experts perceived regulators to be more prepared (than the regulators' self-assessment) for managing risks from nanotechnologies. A similar uncertainty on the part of the regulators was reported in their survey of experts from both the US and Canada, 53 and also by Helland et al, 58 who gathered perceptions of experts from academic, health and safety agency and industry. Another interesting outcome observed from the interviews across the spectrum of expertise was that the questions from one area could promote discussion or even follow-up questions to colleagues from different disciplines.…”
supporting
confidence: 64%
“…For example, the findings are related to outcomes from quantitative studies on expert judgements on risks from chemicals, [45][46][47][48][49] expert perception on nanomaterial regulations, risks, and benefits, [50][51][52][53][54][55] and surveys related to perceptions of risks related to nanomaterials and nanotechnology by industry and other stakeholders. [56][57][58] Given our objectives, a purely qualitative research design was deemed most appropriate for our study, and the findings presented here reflects this approach. Generally, qualitative inquiries are an entry when a field is emerging and little research has been done and there are very few hypothesis to enable influence research policies.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of nanotechnology has raised public concern about potential environmental and human health effects of manufactured nanoparticles (MNPs) released to the environment (Helland et al, 2006;Wiesner et al, 2006). Production of consumer products containing MNPs continues to increase despite the lack of sufficient knowledge concerning how they may affect the environment (Luoma, 2008;Project on Emerging Nanotechnologies, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of TiO 2 nanoparticles has been increasingly reported that the cytotoxicity and genotoxicity in various lines of cultured cells as well as acute toxicity in mice [14][15][16][17][18] . As a result, the discussion about potential risks of nanoparticles has a high priority in governments and the public [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%